Respuesta :
Answer:
M+11=L
Step-by-step explanation:
- M= the weight of Marcia's dog.
- L equals the weight of Lisa's dog.
The weight of Marcia's dog plus 11 = the weight of Lisa's dog.
Answer:
The required variable expression is [tex]L= M + 11[/tex]
Step-by-step explanation:
Consider the provided information.
Let m represent the weight of Marcia's dog.
Let L represent the weight of Lisa's dog.
Lisa's dog is 11 pounds heavier than Marcia's dog.
That means if we add 11 pounds in Marcia's dog weight, the weight of Marcia's dog will be equal to Lisa's dog.
This can be written as:
[tex]L= M + 11[/tex]
Where m represent the weight of Marcia's dog and L represent the weight of Lisa's dog.
Hence, the required variable expression is [tex]L= M + 11[/tex]